The Workers' Bank Limited, Tel-Aviv, Israel : the twenty-seventh annual report : 1948. (Tel-Aviv : Workers' Bank, 1949)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: coöperatieve beweging; Palestina; Israël